2016
DOI: 10.1016/j.agwat.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Drain for Gain: Managing salinity in irrigated lands—A review

Abstract: At present, about 299 Mha (or 18%) of the arable and permanent cropped areas worldwide are irrigated and, although drainage is an important component of irrigation, only 22% of these irrigated lands are drained. As a consequence, salinity and waterlogging problems affect about 10-16% of these areas because the natural drainage is not sufficient for controlling soil salinity levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 47 publications
3
20
0
2
Order By: Relevance
“…The steady increase in canola yield clearly shows that the installation of subsurface drainage can have a very quick payback time. This observation is in agreement with many other studies [47][48][49][50], which showed that subsurface drainage could be an economic activity to improve crop production. Rice yield responded well to the different types of irrigation and drainage management strategies.…”
Section: Crop Yieldssupporting
confidence: 93%
“…The steady increase in canola yield clearly shows that the installation of subsurface drainage can have a very quick payback time. This observation is in agreement with many other studies [47][48][49][50], which showed that subsurface drainage could be an economic activity to improve crop production. Rice yield responded well to the different types of irrigation and drainage management strategies.…”
Section: Crop Yieldssupporting
confidence: 93%
“…Nevertheless, regardless of the significance of drainage, only about 22% of the total irrigated lands are drained globally (Schultz et al, 2007). Salinization progresses rather slowly, therefore stakeholders see irrigation as a need for today and salinization as a problem of tomorrow (Ritzema, 2016). In humid regions drainage is required to control soil water for improved aeration and easier workability, while in arid and semi-arid regions its main purpose is to avoid irrigation-induced salinization of the soil (van Hoorn and van Alphen, 1994).…”
Section: Salinization Of Irrigated Landsmentioning
confidence: 99%
“…Rising groundwater tables and floods are common in humid regions, nevertheless they can also occur in semi-arid and arid regions. These high concentrations of nitrate are not likely to create a health risk now, but if left uncontrolled, will go on to rise, potentially to levels hazardous to health (Singh, 2015c(Singh, , 2016Ritzema, 2016). Water quality due to flooding can also become hazardous.…”
Section: Environmental Perspectivementioning
confidence: 99%
See 2 more Smart Citations